Employee Attitude Surveys in a Multinational Organization: Considering Language and Culture in Assessing Measurement Equivalence - RYAN, Ann Marie (Institutional Knowledge at Singapore Management University, 1999)
The cross-cultural equivalence of a multinational employee opinion survey was examined using multiple-groups covariance structure analysis to examine 4 scales in 4 countries. Cultural and linguistic influences were considered by assessing equivalence across 2 pairs of countries having the same language but different cultures (US and Australia, Mexico and Spain) and across countries differing in culture and language (US and Mexico). The measure was equivalent across US and Australian samples only. Analyses indicated items that were the source of lack of invariance. One cause explored was translation problems. Practical issues in assessing measurement equivalence in employee opinion surveys are discussed.